Practical Null Steering in Millimeter Wave Networks - , Sohrab Madani; Jog, Suraj; Lacruz, Jesus O.; Widmer, Joerg; Hassanieh, Haitham (NSDI'21, 2021)
Millimeter wave (mmWave) is playing a central role in pushing the performance and scalability of wireless networks by offering huge bandwidth and extremely high data rates. Millimeter wave radios use phased array technology to modify the antenna beam pattern and focus their power towards the transmitter or receiver. In this paper, we explore the practicality of modifying the beam pattern to suppress interference by creating nulls, i.e. directions in the beam pattern where almost no power is received. Creating nulls in practice, however, is challenging due to the fact that practical mmWave phased arrays offer very limited control in setting the parameters of the beam pattern and suffer from hardware imperfections which prevent us from nulling interference. We introduce Nulli-Fi, the first practical mmWave null steering system. Nulli-Fi combines a novel theoretically optimal algorithm that accounts for limitations in practical phased arrays with a discrete optimization framework that overcomes hardware imperfections. Nulli-Fi also introduces a fast null steering protocol to quickly null new unforeseen interferers. We implement and extensively evaluate Nulli-Fi using commercial off-the-shelf 60 GHz mmWave radios with 16-element phased arrays transmitting IEEE 802.11ad packets [33] . Our results show that Nulli-Fi can create nulls that reduce interference by up to 18 dB even when the phased array offers only 4 bits of control. In a network with 10 links (20 nodes), Nulli-Fi’s ability to null interference enables 2.68× higher total network throughput compared to recent past work.